Role And Impact Of Digital Media In Spreading News And Information During Pandemic COVID-19 In India - Kumar, Ankit; Sharma, Dr. Trishu (The journal of contemporary issues in business and government, 2021)
Digital Media is always a unique platform for spreading information and using communication technologies in effective ways. As per transmission and impact of information, traditional media (Newspaper, Radio & Television) focus to attention and feedback towards the public. On the other hand Digital Media is not only providing the platform for quick reaction but it makes the user more connected towards content by the changes and usage of information in dynamic ways. During the crises or special circumstance like pandemic digital media played crucial role because of usage and amplifying the information and news regarding COVID-19. This study aims to bring out the impact and role played by digital media during the pandemic and health crises. As per reports the communication technologies especially digital platforms of news are used and viewed at a big scale during this medical emergency around the world. It has been more powerful in professional and business role in democratic countries and liberal nature of media industry like India. This is very clear by the numbers and records of growth in content publishing and advertising profit also.